Quantifying sedimentary ’blue carbon’ in relation to canopy cover in the seagrass meadows of Turneffe Atoll, Belize - Stacey L. Felgate; Richard Sanders; Valdemar Andrade; Christopher D. G. Barry; Hannah Brittain; Stephen Carpenter; Abel Carrias; Eliceo Cobb; Chris D. Evans; James Hunt; Anna Lichtschlag; Daniel J. Mayor; et al. (Frontiers in Marine Science, 2024)
Introduction Seagrass sediments are important ‘blue carbon’ reservoirs which store climatically significant quantities of organic carbon (C org ) at the global scale. Seagrass meadows that overly these sediments also provide a range of critical ecosystem services including shoreline stabilization, storm surge protection, and fisheries nursery grounds. However, the controls over accumulation and the sources of organic C to these sediments beds are highly variable and poorly understood with the relative importance of hydrodynamic setting, species composition and canopy density being unclear. Methods Here we address these questions using the first observation-based estimates of C org stocks and provenance on Turneffe Atoll, Belize, made via remotely-sensed habitat extent, local C org data and isotopic data. Sedimentary C org was highest in sediments underlying the most sheltered meadows and decreased with increasing exposure to wind and wave energy with the seagrass meadows in the central lagoon containing an extensive deposit of mangrove derived organic carbon, stabilized and protected by the overlying seagrass meadow. Results The influence of species composition appeared weak with the ubiquitous species T. testudinum occurring across a wide range of hydrodynamic regimes ranging from the most sheltered to the most energetic and being associated with a wide range of sedimentary organic C concentrations. Importantly from the perspective of remote sensing, org C concentrations were unrelated to canopy density. We hypothesize that this decoupling of organic C concentration from seagrass canopy cover reflects a much longer timescale for carbon storage in the sediments than the lifespan of the seagrass plants themselves and/or a substantial non seagrass derived organic C burden in seagrass sediments. Overall, we conservatively estimate that the top 30cm of sediments underlying the seagrass meadows overlying carbonate sediments on the atoll exterior store 0.58 x 10 6 Mg C org , most of which is seagrass-derived, whilst the sediments underlying the meadows within the central lagoon store an additional 1.28 x 10 6 Mg C org . When the maximum possible extent of seagrass is considered, this estimate increases to 3.54 x 10 6 Mg C org. Substantial C org stocks extending >1m depth were observed across all sites, and so these inventories are considered conservative. Discussion A preliminary ‘cost of loss’ for sedimentary C org in the top 30 cm of Turneffe Atoll’s seagrass meadows, based on a carbon trading value of €60 tCO 2 (eq), is estimated at €42 million for the outer atoll, increasing to €136 million when the mangrove-derived sediments of the central atoll are considered and €260 million when turbid areas are assumed to contain seagrass.